Auditory stimuli suppress contextual fear responses in safety learning independent of a possible safety meaning - Mombelli, Elena; Osypenko, Denys; Palchaudhuri, Shriya; Sourmpis, Christos; Brea, Johanni; Kochubey, Olexiy; Schneggenburger, Ralf (Frontiers in Behavioral Neuroscience, 2024)
Safety learning allows the identification of non-threatening situations, a learning process instrumental for survival and psychic health. In contrast to fear learning, in which a sensory cue (conditioned stimulus, CS) is temporally linked to a mildly aversive stimulus (US), safety learning is studied by presenting the CS and US in an explicitly unpaired fashion. This leads to "conditioned inhibition" of fear responses in which sensory cues can acquire a safety meaning (CS-). In one variant of safety learning, an auditory CS-was shown to reduce contextual fear responses during recall, as measured by freezing of mice. Here, we performed control experiments to test whether auditory stimuli might interfere with freezing by mechanisms other than safety learning ("external inhibition"). Surprisingly, when auditory stimulation was omitted during training (US-only controls), such stimuli still significantly suppressed contextual freezing during recall, indistinguishable from the reduction of freezing after regular safety training. The degree of this external inhibition was positively correlated with the levels of contextual freezing preceding the auditory stimulation. Correspondingly, in fear learning protocols which employ a new context during recall and therefore induce lower contextual freezing, auditory stimuli did not induce significant external inhibition. These experiments show that in safety learning protocols that employ contextual freezing, the freezing reduction caused by auditory stimuli during recall is dominated by external inhibition, rather than by learned safety. Thus, in safety learning experiments extensive controls should be performed to rule out possible intrinsic effects of sensory cues on freezing behavior.